THE INTEGRATION OF FORMATIVE AND SUMMATIVE ASSESSMENT IN ENGLISH LANGUAGE TEACHING - Ramazonova Feruza Akbarovna; Tashmetov Azizbek Ravshan Oʻgʻli (TADQIQOTLAR, 2026)
Article explores the integration of formative and summative assessment in English language teaching, emphasizing the importance of both assessment types in enhancing student learning outcomes. Formative assessment, which occurs during the learning process, provides ongoing feedback to students and teachers, allowing for adjustments in instruction and learning strategies. Summative assessment, conducted at the end of an instructional period, evaluates student learning against specific benchmarks or standards. The article discusses various strategies for effectively combining these assessments, such as using formative assessments to inform summative evaluations and ensuring that both types of assessments align with learning objectives. By integrating formative and summative assessments, educators can create a more holistic approach to evaluating student progress and fostering language development.